INVESTIGATING THE RELATIONSHIP BETWEEN HEPCIDIN LEVELS AND CIRRHOSIS IN PATIENTS WITH CHRONIC LIVER DISEASE - UQAILI , AA; LAGHARI , ZA; SAMO , A; SIDDIQUI , K (Biological and Clinical Sciences Research Journal, 2023)
Iron is an important element in the human body, and hepcidin is a crucial protein that plays a major role in regulating its levels. This protein is particularly important in patients with Chronic Liver Disease (CLD), and its complex interactions with other biomarkers need to be explored further, especially when differentiating between patients with and without liver cirrhosis. In this study, 200 CLD patients with CLD were divided into two groups based on the presence or absence of cirrhosis. The study aimed to investigate the correlation between hecidin levels, serum ferritin, and other iron-related parameters using advanced biochemical assays. The research was conducted over 24 months at a prestigious hepatology research facility. The study found that 65% of patients with cirrhosis had higher Hepcidin levels than those without cirrhosis. Additionally, there was a significant positive correlation between hecidin concentrations and serum ferritin levels, particularly in cirrhosis patients. The findings suggest that hepcidin could play a crucial role in diagnosing and treating CLD, especially in patients with cirrhosis. The multifaceted interactions of hepcidin in patients with cirrhosis could lead to a better understanding of the pathophysiology of CLD.